2021
DOI: 10.3389/fenvs.2021.638324
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Lime and Plant Species Effects on Trace Metals (Copper and Cadmium) in Soil Exchangeable Fractions and Runoff in the Red Soil Region of China

Abstract: The water-soluble heavy metal ions in contaminated soil may enter aquatic ecosystem through runoff, thus causing negative impact on the water environment. In this study, a two-year in situ experiment was carried out to explore an effective way to reduce the runoff erosion and water-soluble copper (Cu) and cadmium (Cd) in a contaminated soil (Cu: 1,148 mg kg−1, Cd: 1.31 mg kg−1) near a large Cu smelter. We evaluated the ability to influence soil properties by four Cu-tolerance plant species (Pennisetum sp., Els… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These results are, in part, consistent with the findings from our previous research (Wyszkowski and Kordala [ 50 ]), which showed that the application of calcium oxide to soil contaminated with gasoline resulted in a decrease in the contents of nickel (11%), cadmium (26.0%), chromium (55.0%) and cobalt (33.0%) compared to the series without the addition of a neutralising material. Xu et al [ 80 ] proved that the addition of lime (0.2%) could significantly reduce the exchangeable fraction of copper and cadmium in soil by 81.1–85.6% and 46.3–55.9%, respectively. Additionally, Vondráčková et al [ 81 ] and Kumarpandit et al [ 82 ] confirmed the effectiveness of the liming process in the in situ stabilisation of contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…These results are, in part, consistent with the findings from our previous research (Wyszkowski and Kordala [ 50 ]), which showed that the application of calcium oxide to soil contaminated with gasoline resulted in a decrease in the contents of nickel (11%), cadmium (26.0%), chromium (55.0%) and cobalt (33.0%) compared to the series without the addition of a neutralising material. Xu et al [ 80 ] proved that the addition of lime (0.2%) could significantly reduce the exchangeable fraction of copper and cadmium in soil by 81.1–85.6% and 46.3–55.9%, respectively. Additionally, Vondráčková et al [ 81 ] and Kumarpandit et al [ 82 ] confirmed the effectiveness of the liming process in the in situ stabilisation of contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Cu mainly accumulates in the surface layer of soils and enters the surface runoff with the process of soil erosion. Then, Cu will accumulate and circulate into rivers, induce water pollution, and endanger the health of aquatic animals and plants . Liu et al investigated 10 large-scale pig farms that digested piggery wastewater in China and found that Cu is detectable in all farms, and its concentrations reached the discharge limit of 0.5 mg/L.…”
Section: Copper and Environmentsmentioning
confidence: 99%
“…Then, Cu will accumulate and circulate into rivers, induce water pollution, and endanger the health of aquatic animals and plants. 104 Liu et al 105 investigated 10 large-scale pig farms that digested piggery wastewater in China and found that Cu is detectable in all farms, and its concentrations reached the discharge limit of 0.5 mg/L. Dos et al 106 also reported that unsustainable agriculture and livestock result in high concentrations of Cu (464.7 mg/kg) in a Doce River tributary in Brazil.…”
Section: Copper and Wastewatermentioning
confidence: 99%